The first phylogeny of Australasian Lamiinae longhorn beetles (Coleoptera: Cerambycidae) reveals poor tribal classification and a complex biogeographic history. (1st November 2021) - Ashman, Lauren G.; Shin, Seunggwan; Zwick, Andreas; Ślipiński, Adam; McKenna, Duane D.
ABSTRACT: We used phylogenomic data and information from the beetle fossil record to reconstruct the phylogeny and historical biogeography of Australasian longhorn beetles (Cerambycidae) in the subfamily Lamiinae. We further focused our study on the distribution of proposed diagnostic morphological characters in Lamiinae, and on the phylogeny of Rhytiphora Audinet‐Serville, Australia's most species‐rich genus of longhorn beetles. Lamiinae was monophyletic, but the majority of tribes were poly‐ or paraphyletic. Within Lamiinae, we recovered four main clades, including one clade mostly comprised of Australian endemic genera of probable Gondwanan origin. This clade also contained taxa that dispersed from Australia to New Zealand and experienced multiple independent instances of wing loss. Another of the four clades contained Australian genera that colonized the region from Asia, including Rhytiphora . The defining feature of Rhytiphora, the setose 'sex patches' on the male abdomen, was shared with many other Asian lamiine genera recovered in the same clade. Our results shed new light on the geographic and temporal origins of Australian Lamiinae, revealing an unexpected mixture of both ancient Gondwanan and recent Asian origins. Moreover, we confirmed rampant nonmonophyly at the tribal level among the Australasian genera of Lamiinae. Based on our results, we move 17 genera into Lamiinae incertae sedis and six genera into the tribe Ancitini Aurivillius. We also reinstate the tribe Niphonini Pascoe for part of the Asian‐Australian Pteropliini Thomson and synonymize Achriotypa Pascoe with Rhytiphora . Abstract : We used anchored hybrid enrichment to estimate the first molecular phylogeny of the Australasian Lamiinae, with an emphasis on the species‐rich genus Rhytiphora Many tribes are not monophyletic, particularly those encompassing endemic Australian genera; we propose an updated tribal classification for these taxa The Australasian Lamiinae have multiple biogeographic origins and evolved winglessness several times independently